Amplification of anti-Diastereoselectivity via Curtin-Hammett Effects in Ruthenium Catalyzed Hydrohydroxyalkylation of 1,1-Disubstituted Allenes: Diastereoselective Formation of All-Carbon Quaternary Centers - Zbieg, Jason R. (2010)
Under the conditions of ruthenium catalyzed transfer hydrogenation, 1,1-disubstituted allenes 1a–1c and alcohols 2a–2g engage in redox-triggered generation of allylruthenium-aldehyde pairs to form products of hydrohydroxyalkylation 3a–3g, 4a–4g and 5a–5g with complete branched regioselectivity. By exploiting Curtin-Hammett effects, good to excellent levels of anti-diastereoselectivity (4:1 – >20:1) are obtained. Thus, all carbon quaternary centers are formed in a diastereoselective fashion upon carbonyl addition from the alcohol oxidation level in the absence of pre-metallated nucleophiles or stoichiometric byproducts. Exposure of allene 1b to equimolar quantities of alcohol 2a and aldehyde 6b under standard reaction conditions delivers adducts 4a and 4b in a 1:1 ratio. Similarly, exposure of allene 1b to equimolar quantities of aldehyde 6a and alcohol 2b provides adducts 4a and 4b in an identical equimolar ratio. Exposure of allene 1b to d(2)-para-nitrobenzyl alcohol, deuterio-2a, under standard reaction conditions delivers the product of hydrohydroxymethylation deuterio-4a, which incorporates deuterium at the carbinol position (>95% (2)H) and the interior vinylic position (34% (2)H). Competition experiments involving exposure of allene 1b to equimolar quantities of benzylic alcohols 2a and deuterio-2a reveal no significant kinetic effect. The collective data corroborate rapid, reversible alcohol dehydrogenation, allene hydrometallation and (E)-, (Z)-isomerization of the transient allylruthenium in advance of turn-over limiting carbonyl addition. Notably, analogous allene-aldehyde reductive C-C couplings employing isopropanol as the terminal reductant display poor levels of anti-diastereoselectivity, suggesting carbonyl addition is not turn-over limiting in reactions conducted from the aldehyde oxidation level.